EVALUATION OF JUNIOR HIGH SCHOOL TEACHER PERFORMANCE: PLANNING, IMPLEMENTATION, AND EVALUATION OF LEARNING - Halim, Babul; Patahuddin, Patahuddin; Suhardi, Iwan (Universitas Labuhanbatu, 2025)
Integrated Junior High School, Tual City, Maluku Province. It focuses on three main aspects: lesson planning, implementation, and evaluation.Methodology – This study employs a descriptive research design and a qualitative approach. Stake's Countenance Evaluation model was used to assess programs. The study evaluated 11 teachers. Data was collected through classroom observation, interviews, and document analysis related to lesson planning, process, and evaluation. Analysis revealed various findings about teacher performance.Findings – Most teachers perform their professional duties effectively. This is demonstrated by the creation of modules, mastery of teaching materials, and the development of assessment instruments. However, some key aspects still need improvement, including planning, process, and evaluation. Although overall performance is good, weak detailed planning and limited innovation in teaching methods and media hinder student attendance, participation, and achievement of minimum competency scores.Contribution – This study can serve as a reference for Al-Ikhlas Integrated Junior High School and other schools to improve teacher performance and education quality.